2021
DOI: 10.7160/aol.2021.130204
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamics of the Social Network of Urban Farmers in Subak Sembung Denpasar

Abstract: A reduction in the number of farmers, urbanization, limited land, poverty, environmental changes, uncertainty of production results and limited access to resources are still being serious problems and have a direct effect on farmers' income. Facing that conditions, in order to survive, social networks are one of the adaptation strategies implemented by the farmers. This research aimed to examine the social phenomena of urban farmers in Subak Sembung, Denpasar City and to try to find the rational actions conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Subak Lestari development can involve transforming subak areas into trekking zones, where residents pay Punia funds (at a specified price) for trekking, managed by the subak or utilizing institutions. This revenue-generating approach mirrors the successful Peken Carik model implemented in Subak Sembung (Darmawan et al, 2021;Wijayanti et al, 2020).…”
Section: Technical Aspectmentioning
confidence: 80%
“…Subak Lestari development can involve transforming subak areas into trekking zones, where residents pay Punia funds (at a specified price) for trekking, managed by the subak or utilizing institutions. This revenue-generating approach mirrors the successful Peken Carik model implemented in Subak Sembung (Darmawan et al, 2021;Wijayanti et al, 2020).…”
Section: Technical Aspectmentioning
confidence: 80%
“…Denpasar City had 12,778 Ha of land that composed of 2,409 Ha (18,85%) of rice paddy field and 510 Ha (3,99%) of non-agricultural land. Studied by Pradnyadewi et al, (2021), Arisena et al, (2020), and Darmawan et al, (2021) identified an urban farming in Denpasar City, namely Subak Sembung. Utilizing the 104 Ha of land areas, Subak Sembung consistently shows vibrant agricultural activities amid Denpasar City.…”
Section: Introductionmentioning
confidence: 99%
“…This research aimed to gather information on Subak in Tabanan, assess the local government's readiness for SDI implementation, and establish a web GIS-based Subak information system for data sharing among government agencies and stakeholders in Tabanan. Previous studies on Subak have primarily concentrated on mapping irrigated rice fields and discerning the socio-economic and cultural aspects of Subak [12][13][14], while SDI has been utilized and evaluated for lahar hazard mitigation and tourism village promotion [7,8]. This research, therefore, holds significant implications for providing Subak data and developing an information system to facilitate the sharing of high-quality Subak data, thereby aiding decision making and the preservation of Subak.…”
Section: Introductionmentioning
confidence: 99%